Property of the parish temple in the 18th – early 20th centuries (based on the materials of the Olonets diocese) - Pulkin Maxim Viktorovich (Institute of Modern Humanitarian Researches, 2021)
Pulkin Maxim Viktorovich – Candidate of Historical Sciences, Senior Researcher of Institute of Language, Literature and History of Karelian Research Center of the Russian Academy of Sciences; Associate Professor of Economics, Production Management and State and Municipal Administration Department, Institute of Economics and Law, Petrozavodsk State University